PELATIHAN HAMICARA JAWA PADA KARANG TARUNA DI KABUPATEN SUKOHARJO - Winda Lestari; Djoko Sulaksono (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Hamicara Jawa or speaking Javanese is one of the language skills that must be preserved and developed, as an effort to maintain and revitalize regional languages among the millennial generation. So, the service team of the Javanesse Education Language Study Program provided good and good hamicarajawa training for youth groups in Sukoharjo district. The method applied is to provide training and mentoring for hamcara Jawa using modeling techniques and direct practice. The result of this service is that youth organizations in the district of Sukoharjo who incidentally still use Javanese as their mother tongue and are used in traditional ceremonies or daily activities can use the good and correct Javanese language. This is in accordance with the purpose of service, namely providing assistance and training to youth youth groups so that they can use good and correct Javanese language in speaking in society, especially hamicara Jawa in community activities and Javanese traditional ceremonies. As an effort to preserve and develop regional languages, especially Javanese, Surakarta style